Associations of clinical biomarker-based biological aging with suicide attempts and suicidal ideation: evidence from 124,529 UK Biobank participants - Wei Hu; Zhenzhen Shen; Ge Tian; Baopeng Liu; Cunxian Jia (Translational Psychiatry)
Abstract Biological aging has been linked to multiple psychological disorders, yet its extrapolation to suicide remains absent. We aimed to examine the associations of biological aging with suicidal ideation (SI) and suicide attempt (SA) and to explore possible moderators of the associations. A total of 124,529 middle and older participants from the UK Biobank were included. Phenotypic age (PhenoAge) indicating biological aging was calculated based on chronological age and nine clinical biomarkers. The residuals of PhenoAge regressed on chronological age were utilized to quantify biological aging, termed PhenoAge acceleration (PAA). Approximately one-third of baseline participants completed mental health follow-up questionnaires including suicide-related information. Multivariate logistic regression models were performed to estimate the associations. 2718 (2.2%) SA and 5207 (4.4%) SI cases were documented. Compared with participants in the lowest quartile of PAA, those in the highest quartile had a 21.8% [odds ratio (OR) = 1.218; 95% confidence interval (CI): 1.087–1.198) and 12.5% (OR = 1.125, 95% CI: 1.035–1.224) higher odds of SA and SI, respectively. Biologically older participants (PAA > 0) were more likely to report SA (OR = 1.104, 95% CI: 1.018–1.198) and SI (OR = 1.064, 95% CI: 1.003–1.129). Gender, age, socioeconomic status (SES), physical activity, and somatic and psychiatric disorders could modify the associations (P for interaction <0.05). Our findings indicated that PAA-measured aging might be positively associated with SA/SI. Interventions aimed at slowing aging might contribute to suicide prevention, especially among males, young adults, low SES, the physically inactive, and vulnerable populations.